Research Papers on Leather Science: A Bibliometric Study - Basak, Anita; Bandyopadhyay, Ratna (Qualitative and Quantitative Methods in Libraries, 2017)
The bibliometric methods used and results given to satisfy the information needs of users form the basis of this paper. In this paper, we identify the major and emerging areas of research in leather science, core journals in specific areas, leading scientists in specific areas, and important institutions contributing to different fields. For the above we have used bibliometric techniques like trend analysis, h-index, h5-index, hmedian, g-index, Eigenfactor score, Article Influence score, Thompson Impact factor and others at different times. Various sources have been used like journals – both printed and online, Web of Science, Scopus, Google Scholar etc.